Correlation Study Using Scuffing Damage to Investigate Improved Simulation Techniques for Packaging Vibration Testing. (2nd July 2012) - Griffiths, K.; Shires, D.; White, W.; Keogh, P. S.; Hicks, B. J.
<x xml:space="preserve">Abstract</x> Vibration testing of packaging is a critical part of the distribution packaging analysis process. The accuracy of simulated vibration is important for packaging optimization. Because of this, several researchers have developed improved simulation methods to produce more realistic vibration tests. Correlation studies are required to verify these methods, ideally using actual packaged products in transit. Unfortunately, cost, time and complexity issues make carrying out studies with actual product difficult. This article uses a specially designed and proven test rig, which simulates the damage mechanism of scuffing, to carry out a correlation study. The study compares the level of damage produced when performing simulations using a range of improved techniques in comparison with the time‐history reproduction of a journey (used as a benchmark) and the established method using the average power density spectrum to create a Gaussian simulation signal. The level of scuffing damage produced varied between the different simulation methods, with the modulated root mean square (RMS) technique and the accelerated power density spectrum (with a time compression of 5 and a k equal to 2) best reproducing the level of damage observed from the benchmark time replication test. Copyright © 2012 John Wiley & Sons, Ltd.